Efektivitas Penerapan Model Project-Based Learning pada Mata Pelajaran Pekerjaan Dasar Elektromekanik - Bima Andesko; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to determine the effectiveness of implementing the project-based learning model and student learning outcomes after implementing learning using the PJBL model in basic electromechanical work subjects at SMK Negeri 5 Padang. Student learning outcomes are still low which is caused by learning factors that are still teacher-centered, thus affecting student learning outcomes in the cognitive and psychomotor domains. Therefore, it is necessary to apply a project-based learning model to find out how effective this learning model is on student learning outcomes. This research uses a type of experimental research which is categorized into a type of quasi-experimental research with a one-group pretest posttest design. The object of this research is the project-based learning model and the effectiveness of its application on student learning outcomes in basic electromechanical work subjects. The subjects of this research were students of class X TITL SMKN 5 Padang. The research instruments used were pretest and posttest questions in objective form and practical assessment sheets. Based on the average score of the posttest and practice worksheets, it is in the high category. Therefore, the application of project-based learning as a learning model in basic electromechanical work subjects is said to be effective because the classical value and effect size are included in the high category.